Systems integration: A tool for project monitoring in the public sector / Noriati Baharum - Noriati , Baharum (2000)
Many computerized systems today operate within organizational boundaries. In the Malaysian public sector, early systems were developed to solve organizational business functions. In the course of developing application systems to resolve specific needs, these organizations hardly look beyond the boundaries of their business domain. This phenomenon led to the existence of islands of information systems within the government sector. In this study, the researcher proposed to look into the issues of systems integration (SI) within the public sector, in general and subsequently proceed to an area where SI is deemed to be appropriate. Project monitoring for the government in Malaysia is an important matter. It is vital ensure projects that are planned for the development of the country is implemented according to schedule. Proper management and monitoring of these projects are essential to their success. In compliance with procedures, several government departments are involved in the course of a project development. As such, the handling of project information across these departments is an area where the researcher feels SI could be effectively deployed. To provide the researcher with a broad perspective of SI in the public sector, a survey is conducted amongst departments deploying information technology (IT) in their daily operations. This survey looks into methods of data-sharing amongst government bodied and measures the extent of SI adoption amongst them/ it also looks at issues surrounding SI within the government sector. Literatur study is done to lay the ground work in applying SI solutions to these information islands. It provides the researcher with some theoretical framework in order to progress including getting information in works done on this subject and current trends. Discussions on the case study are illustrated through a prototype of a serves to demonstrate the researcher’s proposed tool for project monitoring in an integrated environment. In order to further support the proposed solution, an assessment of the prototype was conducted among users familiar with the subject of project monitoring in the government.